Onward we charge the heroic story of Darby's Rangers in World War II - Jeffers, Harry Paul 1934- (Nal Caliber, 2007)
Awarded the Distinguished Service Cross and the Purple Heart, and posthumously promoted to Brigadier General by President Truman, Colonel William Darby was an indisputable hero. His elite battalion of Army Rangers paved the way for Ranger success in subsequent wars, and left an unforgettable legacy in its wake. This book takes readers from the beachheads of North Africa to the bloody campaigns of southern Italy, and to Darby's tragic death by German shrapnel just eight days before V-E Day. This is the true story of a man who held his own beside the greatest military figures in history.--From publisher description.